2008
DOI: 10.2139/ssrn.1301100
|View full text |Cite
|
Sign up to set email alerts
|

Decisions from Experience and the Effect of Rare Events in Risky Choice

Abstract: ABSTRACT-When people have access to information sources such as newspaper weather forecasts, drug-package inserts, and mutual-fund brochures, all of which provide convenient descriptions of risky prospects, they can make decisions from description. When people must decide whether to back up their computer's hard drive, cross a busy street, or go out on a date, however, they typically do not have any summary description of the possible outcomes or their likelihoods. For such decisions, people can call only on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
256
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(275 citation statements)
references
References 16 publications
16
256
1
2
Order By: Relevance
“…Because the model-predicted ratings update based on experience, they were also better able to predict the post-experiment probability ratings than the initial trustworthiness ratings. These findings support and extend previous research, which has found that experience overwhelms description in risky choice (Barron & Erev, 2003;Hertwig, Barron, Weber, & Erev, 2004;Jessup, Bishara, & Busemeyer, 2008). While this notion of dynamically updating beliefs is certainly not new, this study provides, to our knowledge, support for the first computational model of this effect in an iterative social exchange.…”
Section: Modeling Trustsupporting
confidence: 90%
“…Because the model-predicted ratings update based on experience, they were also better able to predict the post-experiment probability ratings than the initial trustworthiness ratings. These findings support and extend previous research, which has found that experience overwhelms description in risky choice (Barron & Erev, 2003;Hertwig, Barron, Weber, & Erev, 2004;Jessup, Bishara, & Busemeyer, 2008). While this notion of dynamically updating beliefs is certainly not new, this study provides, to our knowledge, support for the first computational model of this effect in an iterative social exchange.…”
Section: Modeling Trustsupporting
confidence: 90%
“…How people learn about choice options influences their preferences and consequently their risk-taking behavior (see Barron & Erev, 2003;Denrell, 2007;Erev & Barron, 2005;Hertwig et al, 2004;March, 1996;Weber et al, 2004). During the Iowa Gambling Task (Bechara et al, 1994), the learning process even dissociates between different clinical populations and the risks they take.…”
Section: Learningmentioning
confidence: 99%
“…It can, for example, create an aversion toward risky alternatives in the gain domain and an attraction toward risky alternatives in the loss domain-a pattern typically attributed to how DMs evaluate outcomes (Denrell, 2007;March, 1996). The learning process can even produce the opposite pattern (Erev & Barron, 2005;Hertwig, Barron, Weber, & Erev, 2004;Weber, Shafir, & Blais, 2004).Applying theories of decision making to the Balloon Analogue Risk Task (BART; Lejuez et al, 2002) or to the Iowa Gambling Task (Bechara, Damasio, Damasio, & Anderson, 1994) also exposes the necessity of learning. Clinicians use these laboratorybased gambling tasks to study and identify people with specific clinical or neurological deficits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Judgments (probability estimations) appear to reflect over-sensitivity to rare events (Erev, Wallsten et al 1994). On the other hand, decision-making from experience tends to reflect underweighting of (insensitivity to) rare events (Barron and Erev 2003, Hertwig, Barron et al 2004, Weber, Shafir et al 2004). …”
Section: Introductionmentioning
confidence: 99%